Perancangan Sistem Booking Kamar pada Instalasi Rawat Inap Guna Menunjang Efektifitas Registrasi Pasien di Rumah Sakit Jiwa Provinsi Jawa Barat - Rizki, Muhamad; Syahidin, Yuda; Sari, Irda (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The rapid development of information technology has had a huge impact on many things around us. This study aims to create effective patient registration by designing and developing systems to support better service in the hospital environment. In line with the objectives that the researchers have outlined, the problem behind this study is the inefficiency of patient registration when carrying out health care when researchers carry out field practice. As for the method of this study, it is a waterfall, which will produce an updated application output and can support the effectiveness of patient care. Based on this research, the researchers suggest that in order to improve the efficiency of hospital services, medical records should be able to develop existing systems and work with the field of system development to get more optimal results.